The noun phrase in English : past and present - Leung, Alex Ho-Cheong; Wurff, Wim van der (Linguistik aktuell, 2018)
"Building on a substantial earlier literature, the chapters in this volume further advance knowledge and understanding of properties of the noun phrase in English. The empirical material for the papers includes both historical and present-day data, with the two often shedding light on each other in a process of mutual illumination. The topics addressed are: the structure of nounless NPs like the poor and the obvious; the article/zero alternation in expressions like go to (the) church; developments in the early history of adjective stacking; the semantics of N + clause units in present-day English; the history of N + BE + clause constructions; and the decline of two anaphoric NPs in Early Modern English. The volume will appeal to scholars working in this area and will also help those interested in the general field of English grammar to keep abreast of recent methods and results in NP-related work"--